EFL Students’ Perceptions of Collaborative Writing during Remote Teaching - Yanti Sri Rezeki; Surmiyati Surmiyati (Jurnal Pendidikan Bahasa, 2021)
Whether online or face-to-face, research on collaborative writing has been widely conducted to explore its theoretical and pedagogical merits for language learning. Despite positive evidence on its benefits, more studies need to explore its implementation under specific circumstances such as teaching and learning during the pandemic Covid-19. This paper reports the EFL pre-service teachers’ perceptions and attitudes of their experiences and perceived affordances of collaborative writing toward their language and soft skill development. Data were gathered from the three questionnaires administered after students finished their collaborative writing projects: poetry infographic, descriptive text, and discussion text. Additionally, students’ reflective notes after completing all tasks were used to triangulate the data. The findings showed students’ positive perceptions of their collaborative writing experiences across the three text genres. The study also revealed students’ agreement on the affordances of collaborative writing for their language and soft skill development. Pedagogical implications are also discussed.